Development of higher-order thinking skills oriented to illustrated multiple choice questions using a contextual approach to chemical equilibrium materials - Aulia, Adinda Fara; Rahmawan, Setia (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2025)
This study aims to develop HOTS-oriented pictorial multiple-choice questions with a contextual approach to chemical equilibrium material, which means linking surrounding phenomena with real objects. This type of research is Research and Development using the Tessmer model, which consists of preliminary stages, self-evaluation stages, prototyping stages and field test stages. The results of the study showed that the HOTS test instrument was said to be valid based on the results of the Content Validity Ratio and Content Validity Index, producing a value of 1.00 with a good category, then the HOTS test instrument had high reliability with a Cronbach alpha value of 0.84. The high-level thinking skills of students were at an excellent level, namely 16.43%, good 27.09%, sufficient 35.43%, lacking 43.76%, and significantly lacking 10.42% of the 67 students involved in the field test. The average score of high-level thinking skills is 48, with a sufficient category. The final result obtained 20 valid and reliable HOTS questions, and the HOTS test instrument can measure students' critical thinking skills.